Classification Evolution, Control Strategy Innovation, and Future Challenges of Vehicle Suspension Systems: A Review - Mei, Yixin; Wang, Ruochen; Ding, Renkai; Jiang, Yu (Actuators, 2025)
The suspension system can adapt to different road excitations by adjusting its own stiffness or damping, or outputting active driving force, thereby improving the comprehensive dynamic performance of the vehicle, including ride comfort and vehicle handling. As the automotive industry’s requirements for “intelligence, comfort, and safety” continue to increase, the intelligence of suspension systems has become a research hotspot for scientific research institutions and enterprises, with broad development prospects. This article reviews the current development status of automotive suspensions and introduces the working principles and research status of different types of suspension systems, such as passive suspensions, semi-active suspensions, active suspensions, and electromagnetic suspensions. In addition, it summarizes the control methods of vehicle intelligent suspensions, including classical control, modern control, and intelligent control, and expounds the advantages and disadvantages of each control strategy. Finally, it summarizes the challenges and development trends faced by suspension systems. This review can provide technical reference for researchers engaged in the study of intelligent suspension under the modern chassis architecture and offer direction guidance for the development of key suspension technologies.